Enhancing the Extraction of 6-Gingerol from Zingiber officinale Rhizomes Using Dry Vacuum Evaporation to Improve Bioavailability - I, Okafor A.; O, Ogar B. (African Journal of Biochemistry and Molecular Biology Research, 2024)
This study optimized the extraction and purification of 6-gingerol from ginger (Zingiber officinale) rhizomes through a multi-step process. Initially, cold maceration ethanol extraction was performed, followed by hexane defatting to remove impurities. Further purification was achieved through liquid-liquid extraction using a sequential solvent system of chloroform and ethyl acetate. The resulting extract was then fractionated using silica gel column chromatography with methanol, and finally concentrated using dry vacuum evaporation to minimize heat-induced degradation. HPLC analysis confirmed a significant concentration of 6-gingerol (33 mg/g) in the final extract. Thus, optimized method demonstrates an effective approach to produce high-quality ginger extracts enriched in 6-gingerol, with potential applications in pharmaceutical or nutraceutical products.